Online education in palliative care - A national exploratory multimethod study - Carina Lundh Hagelin; Christina Melin-Johansson; Jane Österlind; Birgitta Bisholt; Susanna Pusa (BMC Palliative Care)
Abstract Background With an increased number of people living with multiple progressive diseases, online education courses have been created to address the growing need for competence in palliative care. However, there is limited knowledge about the form and content of these courses, or of participants’ experiences. This study aims to map the status, content, and evaluation of online palliative care courses in Sweden. Methods This exploratory study used both quantitative and qualitative methods. The study process involved searching for online palliative care courses on the web and through contact with Swedish palliative care organisations, and then participating in these courses, surveying education providers, and analysing and validating responses. Quantitative data were analysed using descriptive statistics, while thematic analysis was applied to the free-text responses. Results Nine online courses provided by five different organisations were mapped. These courses educated over 30 000 healthcare professionals, predominantly assistant nurses and registered nurses. There was a large discrepancy between the number of people who enrolled in and the number who completed the online courses. Shortcomings identified related to lack of systematic evaluation from the participants’ perspectives, if and how knowledge was integrated into clinical practice, and difficulties in making the courses sustainable. Conclusion Overarching and national systems for online education are needed. These would require sustainability considerations and guidelines for implementation, evaluation and follow-up of non-university-based online educational initiatives in palliative care. In addition, it is crucial for employers to support professionals undergoing such education, ensuring that they are given opportunities to share their feelings and discuss any challenging thoughts that arise during and after the course.